Storytelling as a transformative tool: how narrative-based teaching reshapes clinical education outcomes in vocational nursing internships - Xiao, Le; Peng, Deqing; Zhong, Jindan; Fang, Tanglin; Dai, Lei; Peng, Xuyun; Yu, Chengying; Huang, Feiyan (Frontiers in Medicine, 2025)
BackgroundTraditional clinical apprenticeships in Chinese vocational nursing education often inadequately address professional identity development. This study evaluates the effectiveness of narrative pedagogy in enhancing professional identity and clinical competencies among vocational nursing interns.ObjectiveTo evaluate the impact of narrative teaching interventions on two primary outcomes: professional identity development and clinical competency acquisition among vocational nursing interns.MethodsUsing stratified cluster randomization, 82 clinical interns from a tertiary hospital were allocated to either: Observation group (n = 42) received biweekly narrative teaching sessions incorporating storytelling, role-playing, reflective writing, and clinical application cycles. Control group (n = 40) standard one-on-one apprenticeship training. Post-intervention evaluations utilized the Nurse Professional Identity Scale, the Nursing Intern Core Competency Scale, and a custom teaching evaluation form.ResultsThe observation group significantly outperformed the control group in professional identity and core competency dimensions (P < 0.001), with notable improvements in personal traits and clinical skills. They also excelled in learning interest, teamwork, and clinical thinking (P < 0.05).ConclusionNarrative-based teaching enhances vocational nursing students’ professional identity, competencies, and internship quality, offering a valuable model for emotional and professional development.